PENGARUH PEMBERIAN VITAMIN B1 DAN JUMLAH RUAS TERHADAP PERTUMBUHAN BIBIT LADA (Piper nigrum L.) - Syahrani; Eka Rahmawati; David Herlinton Sitohang (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2022)
This study aims to determine the effect of Vitamin B1 and the number of segments on the growth of pepper (Piper nigrum L.) seedlings. This research was started from January to March 2021, located in Siram Makmur Village, Bongan District, West Kutai Regency, East Kalimantan Province. This study was arranged in a Randomized Complete Block Design (RCBD) with 6x3 factorial analysis, each factor was repeated 3 dan the concentration of Vitamin B1 as the first factor (B) consisted of 6 levels, namely (b₀) control, (b₁) 1 mg Vitamin B1, (b₂) 2 mg Vitamin B1, (b) 3 mg Vitamin B1, (b₄) 4 mg Vitamin B1, (b₅) 5 mg Vitamin B1. For the number of segments as the second factor (P) consists of three levels, namely (p₁) 1 segment, (p₂) 2 segments, and (p₃) 3 segments. The effect of giving Vitamin B1 had no significant effect on the observation parameters, the time of shoot emergence, the fastest result was the treatment of 3 mg Vitamin B1 (b3) which was 24.77 days and the late result was the treatment of 5 mg Vitamin B1 (b5) which was 26 days, for the total shoots, the highest yield was treatment of 2 mg and 4 mg of Vitamin B1 (b2),(b4) which was 4 shoots and the least yield was treatment of 2 mg of Vitamin B1 (b1) which was 3 shoots, for the number of leaves, the highest yield was treatment of 4 mg Vitamin B1 (b4) is 7.66 leaves and the least yield is treatment of 3 mg Vitamin B1 (b3) which is 6.33 leaves and for plant height, the highest yield is treatment of 2 mg Vitamin B1 (b2) which is 8.46 cm and the lowest result was the treatment of 5 mg of Vitamin B1 (b5) which was 7.06 cm. The treatment of the number of segments had no significant effect on the observation parameters, the time of emergence of shoots, the fastest result was the treatment of two segments (p2) which was 24.77 days and the late result was the treatment of three segments (p1) which was 25.72 days, for the number of shoots, the results the most was the treatment of two segments (p2), namely 3.83 shoots and the least yield was the treatment of one segment (p3), namely 3.16 shoots, for the number of leaves, the highest yield was the treatment of two segments and three segments (p2), (p3) ie 7 leaves and the least yield is treatment (p1) which is 6.83 leaves and for plant height, the highest yield is treatment of one segment (p1) which is 7.97 cm and the shortest result is treatment (p2) which is 7.63 cm . The best interaction results on the treatment parameters of Vitamin B1 and the number of internodes based on observations, for the time of shoot emergence the fastest interaction was the control treatment and one segment (b0p2) which was 24 days, for the number of shoots, the most interaction results were the treatment of 4 mg Vitamin B1 and one internodes, two segments, and three segments (b4p1), (b4p2), (b4p3) which is 4, for the number of leaves, the most interaction results are control and two internode treatment, 4 mg Vitamin B1 and one segment, 5 mg Vitamin B1 (b0p2 ), (b4p1), (b5p2) which is 9 strands and for plant height, the highest interaction result is treatment of 2 mg Vitamin B1 and one segment (b2p1) which is 8.93 cm.